The importance of human ecology to the understanding of women´s homelessness - Sónia Nobre (Forum Sociológico)
This article draws on part of my research on women´s homelessness, which was conducted for my PhD in human ecology, to explain the importance of a human ecological lens for a broader understanding of this phenomenon. Specifically, the article highlights the usefulness of an overarching ecological approach for a fuller understanding of women´s homelessness in theoretical and empirical terms. Moreover, based on some research findings, it is argued that an ecological approach, combined with a life course perspective, which guided an in-depth and comprehensive analysis of participants´ biographical data, enabled a more complete understanding of these women´s lives and how their homelessness came about. Overall, the relevance of this article lies in the adoption of an ecological view of women´s homelessness, which contributes to a more holistic knowledge of this under-researched subject.